Regulation of reactive oxygen species-mediated abscisic acid signaling in guard cells and drought tolerance by glutathione - Munemasa, Shintaro; Muroyama, Daichi; Nagahashi, Hiroki; Nakamura, Yoshimasa; Mori, Izumi C.; Murata, Yoshiyuki (Frontiers in Plant Science, 2013)
The phytohormone abscisic acid (ABA) induces stomatal closure in response to drought stress, leading to reduction of transpirational water loss. A thiol tripeptide glutathione (GSH) is an important regulator of cellular redox homeostasis in plants. Although it has been shown that cellular redox state of guard cells controls ABA-mediated stomatal closure, roles of GSH in guard cell ABA signaling were largely unknown. Recently we demonstrated that GSH functions as a negative regulator of ABA signaling in guard cells. In this study we performed more detailed analyses to reveal how GSH regulates guard cell ABA signaling using the GSH-deficient Arabidopsis mutant cad2-1. The cad2-1 mutant exhibited reduced water loss from rosette leaves. Whole-cell current recording using patch clamp technique revealed that the cad2-1 mutation did not affect ABA regulation of S-type anion channels. We found enhanced activation of Ca2+ permeable channels by hydrogen peroxide (H2O2) in cad2-1 guard cells. The cad2-1 mutant showed enhanced H2O2-induced stomatal closure and significant increase of ROS accumulation in whole leaves in response to ABA. Our findings provide a new understanding of guard cell ABA signaling and a new strategy to improve plant drought tolerance.